Childhood Adversity Is Associated With Increased KITLG Methylation in Healthy Individuals but Not in Bipolar Disorder Patients - He, Yujie; Vinkers, Christiaan H.; Houtepen, Lotte C.; de Witte, Lot D.; Boks, Marco P. (Frontiers in Psychiatry, 2019)
Backgrounds Childhood adversity increases the risk of a range of mental disorders including bipolar disorder, but the underlying mechanisms are still unknown. Previous studies identified DNA methylation levels at the cg27512205 locus on the KIT Ligand (KITLG) gene as a mediator between childhood adversity and stress responsivity. This raises the question whether this locus also plays a role in stress related disorders such as bipolar disorder. Therefore, the current study aims to compare the level of KITLG (cg27512205) methylation between bipolar patients and healthy individuals and its relation to childhood adversity. Methods KITLG (cg27512205) methylation was measured in 50 bipolar disorder patients and 91 healthy control participants using the HumanMethylation450K BeadChip platform. Childhood adversity in each individual was assessed using the Childhood Trauma Questionnaire. Analyses of the association of KITLG methylation with bipolar disorder, the association of childhood adversity with bipolar disorder as well as the association of KITLG methylation with childhood adversity in bipolar patients and controls were conducted using linear regression with age, gender, childhood adversity, smoking and cell-type composition estimates as covariates. Results KITLG (cg27512205) methylation level was significantly lower in bipolar disorder patients (β = -0.351, t = -6.316 p < 0.001). Childhood adversity levels were significantly higher in the bipolar disorder group (β = 4.903, t = 2.99, p = 0.003). In the bipolar disorder patients KITLG methylation was not associated with childhood adversity (β = 0.004, t = 1.039, p = 0.304) in contrast to the healthy controls (β= 0.012, t = 3.15, p = 0.002). Conclusions KITLG methylation was lower in bipolar disorder despite high levels of childhood adversity, whereas childhood adversity was associated with higher KITLG methylation in healthy controls. In addition to lower methylation at this locus there is an indication that failure to adjust KITLG methylation to high levels of childhood adversity is a risk factor for bipolar disorder.